Security determinants in building automation system - Shuib, Mohd Syamsyul; Ali, Maisarah (IIUM Press, 2017)
Building automation systems (BAS) are an important part of modern automated buildings. This system ensures the operational performance of the facility as well as functions affecting occupant’s safety, security and health. Contemporary industrial control systems no longer operate in isolation, but use other networks (e.g., corporate networks and the Internet) to facilitate and improve business processes. The consequence of this development is the increased exposure to cyber threats on top of existing physical security threat. This research sought to identify the relationship of security determinant in Building automation system which may compromise the safety of occupant or functionality of the building. This study used quantitative research method supported by Likert-scaled survey questionnaire as a quantitative data collection. The dependent variable is BAS security and the independent variables involved are management commitment, security awareness, competency and policy and procedure. Pilot study was done by administering the questionnaire to respondents who were selected randomly and data analysis has been done through SPSS software. The data collected was presented in through charts and tables for easy analysis. The correlation analysis proved that the independent variables (management commitment, security awareness, competency and policy and procedure) are positively correlated with the BAS security. In addition, the correlation between competency and management commitment, security awareness and policy and procedure was also analyses and also shown a very positive correlation. The thorough knowledge of security determinant will assist in developing functional and secured BAS environment while meeting security objectives.